Challenges in the diagnosis of arterial hypertension in consulting room - Quiroz, Guillermo (2006)
We review some important factors to consider when assessing a patients blood pressure and the factors for a correct hypertension diagnosing, in order to avoid over or under diagnosis. We review the terms episodic hypertension, white coat hypertension, masked_ hypertension and other concepts.